1984
DOI: 10.1111/j.1476-5381.1984.tb16232.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and biliary excretion of bromosulphophthalein, [3H]‐ouabain and [3H]‐taurocholic acid in rats with glycerol‐induced acute renal failure

Abstract: 1 The pharmacokinetics and biliary excretion of bromosulphophthalein (BSP), ouabain and taurocholic acid (TChA) have been studied in rats with glycerol-induced acute renal failure (ARF). 2 In rats with ARF, the hepatic uptake and initial biliary excretion of BSP were decreased. In addition, the rate of BSP conjugation with glutathione by rat liver homogenates was also decreased. This latter change may contribute to the initial decrease in the biliary excretion of BSP. 3 No change was found in the hepatic uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Studies showed that the hepatic uptake and initial biliary excretion of bromosulfophthalein were decreased in rats with glycerol-induced acute renal failure (Bowmer and Yates, 1984). A similar phenomenon was observed for another organic anion, indocyanine green (Yates et al, 1983).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Studies showed that the hepatic uptake and initial biliary excretion of bromosulfophthalein were decreased in rats with glycerol-induced acute renal failure (Bowmer and Yates, 1984). A similar phenomenon was observed for another organic anion, indocyanine green (Yates et al, 1983).…”
Section: Discussionsupporting
confidence: 48%
“…The effects of renal failure on hepatic uptake of organic anions were documented in early studies (Yates et al, 1983;Bowmer and Yates, 1984). Studies showed that the hepatic uptake and initial biliary excretion of bromosulfophthalein were decreased in rats with glycerol-induced acute renal failure (Bowmer and Yates, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing awareness that uptake transport of drugs across the sinusoidal membrane of hepatocytes regulates the access of drug substrates to hepatocelluar enzymes as well as canalcular transport into the bile canaliculi, and can be a rate-limiting step in the overall process of hepatic drug clearance. 46 In 1984, Bowmer, Yates and their colleagues 47 , 48 47 , 48 reported that the hepatic uptake of two anionic dyes (indocyanin green and bromosulfophthalein) that are non-selective OATP substrates were reduced in acute renal failure rats. The functional and clinical significance of these findings did not become evident until a series of recent investigations showed that inhibition of uptake transport into the liver may explain to a large extent the reduced non-renal clearance observed in CKD patients for several commonly used drugs that are moderately good to high affinity substrates of human hepatic OATPs: erythromycin, 9 , 49 eprosartan, 50 fexofenadine, 8 and digoxin.…”
Section: Drug Transport In Ckdmentioning
confidence: 99%
“…BSP was measured according to established techniques by measuring its absorption in a spectrophotometer (Cecil 2020, ultraviolet/ visible light spectrophotometer) at 570 nm [10]. The colour of BSP may degrade upon exposure to air and, in order to minimise this, a glycine-NaOH buffer pH=10.0 was added to each sample.…”
Section: Bsp Assaymentioning
confidence: 99%